Identification of differentially expressed proteins from Leishmania amazonensis associated with the loss of virulence of the parasites. - Rubens D M Magalhães; Mariana C Duarte; Eliciane C Mattos; Vivian T Martins; Paula S Lage; Miguel A Chávez-Fumagalli; Daniela P Lage; Daniel Menezes-Souza; Wiliam C B Régis; Maria J Manso Alves; Manuel Soto; Carlos A P Tavares; et al. (Public Library of Science (PLoS), 2014)
BACKGROUND: The present study analyzed whether or not the in vitro cultivation for long periods of time of pre-isolated Leishmania amazonensis from lesions of chronically infected BALB/c mice was able to interfere in the parasites' infectivity using in vivo and in vitro experiments. In addition, the proteins that presented a significant decrease or increase in their protein expression content were identified applying a proteomic approach. METHODOLOGY/PRINCIPAL FINDINGS: Parasites were cultured in vitro for 150 days. Aliquots were collected on the day 0 of culture (R0), as well as after ten (R10; 50 days of culture), twenty (R20; 100 days of culture), and thirty (R30; 150 days of culture) passages, and were used to analyze the parasites' in vitro and in vivo infectivity, as well as to perform the proteomic approach. Approximately 837, 967, 935, and 872 spots were found in 2-DE gels prepared from R0, R10, R20, and R30 samples, respectively. A total of 37 spots presented a significant decrease in their intensity of expression, whereas a significant increase in protein content during cultivation could be observed for 19 proteins (both cases >2.0 folds). Some of these identified proteins can be described, such as diagnosis and/or vaccine candidates, while others are involved in the infectivity of Leishmania. It is interesting to note that six proteins, considered hypothetical in Leishmania, showed a significant decrease in their expression and were also identified. CONCLUSIONS/SIGNIFICANCE: The present study contributes to the understanding that the cultivation of parasites over long periods of time may well be related to the possible loss of infectivity of L. amazonensis. The identified proteins that presented a significant decrease in their expression during cultivation, including the hypothetical, may also be related to this loss of parasites' infectivity, and applied in future studies, including vaccine candidates and/or immunotherapeutic targets against leishmaniasis.